Accounting policies as a tool to ensure solvency in the general insurance business / Leelawati Ibrahim - Ibrahim, Leelawati (1990)
"Accounting", according to the "Accounting Terms Dictionary" is the process of identifying, measuring and communicating economic information about an entity to permit informed judgments and decision by user of the information.